Affecting Factors BPJS Users on the Tiered Referral System in the Pokenjior Community Health Center, Padang Sidempuan City - Ria Hartaty; Sri Lestari Ramadhani Nasution; Ali Napiah Nasution; Ermi Girsang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the factors that influence BPJS users of the Tiered Referral System in the Work Area of Pokenjior Health Center, Padangsidimpuan City. This research is an analytical research type with explanatory research type. The populations in this study were all BPJS users or patients undergoing health services at the Pokenjior Public Health Center in Padang Sidempuan City with a sample of 98 patients participating in the Health BPJS. Data were collected using a questionnaire and analyzed using the Pearson Correlation test and multiple logistic regression tests. The results showed that there was an influence of BPJS user knowledge (p = 0.007), officer attitudes (p = 0.003), availability of infrastructure and human resources (p = 0.002), and referral information (p = 0.003) to the tiered referral system at Pokenjior Public Health Center. The results of multivariate analysis and modeling show that BPJS user knowledge, availability of infrastructure, and human resources and referral information are the dominant factors influencing the tiered referral system. Thus it was concluded that the knowledge factor of BPJS users, the availability of infrastructure and human resources as well as the referral information had a significant effect on the tiered referral system in Pokenjior Public Health Center, and the availability of infrastructure and human resources was the biggest or most dominant factor affecting the tiered referral system in the work area Pokenjior Public Health Center in Padangsidimpuan City